Egg Baked in Product Open Oral Food Challenges are Safe in Selected Egg-Allergic Patients - Becky J. Buelow M.D. M.S.; Carrie Lee A.P.N.P.; Heidi T. Zafra M.D.; Mahua Dasgupta M.S.; Ray G. Hoffmann Ph.D.; Monica Vasudev M.D. (Allergy & Rhinology, 2014)
Egg allergy is one of the most common food allergies in children. Most egg-allergic children are able to tolerate egg baked in product (EBP) and will likely outgrow his/her egg allergy. By introducing EBP in the diet of an egg-allergic child, diet can be expanded and family stress can be reduced. Recent evidence suggests that children who tolerate EBP and continue to consume it will have quicker resolution of egg allergy than those who strictly avoid EBP; therefore, we aimed to evaluate the egg-allergic children who underwent EBP oral food challenge (OFC) in our allergy clinic to help define any specific predictors to be used in predicting the outcome of such challenges. We performed a retrospective chart review and 43 egg-allergic patients underwent EBP OFC in our outpatient allergy office from January 2011 to December 2012 were excluded. Nine patients who did not have a prior history of symptomatic egg ingestion. Clinical characteristics and laboratory findings of the remaining 34 patients were all recorded and analyzed. Of the remaining 34 patients, 22 (64.7%) were boys. Average age of first reaction to egg was 12.90 months, with average age at EBP OFC of 71.32 months. The average of the most recent skin-prick test wheal size was 10.10 mm and serum-specific IgE to egg white was 3.21 kU/L. Twenty-eight of the 34 patients (82.4%) passed the EBP OFC. Of the six patients who failed, none required epinephrine. After analysis of all of the clinical characteristics and laboratory findings, no risk factors, such as skin-prick test wheal size, were identified to be associated with an increased risk of failing EBP OFC. EBP OFC is a valuable tool to assess tolerance. As seen in our group of patients, the majority of egg-allergic patients pass EBP OFC. Thus, OFC should be considered as a clinical tool to expand a patient's diet and to improve quality of life as early as possible. Because we were unable to determine any clinical or laboratory predictors helpful to select egg-allergic patients who are likely to pass EBP OFC, additional prospective studies are necessary to determine the ideal egg-allergic patient who is likely to pass EBP OFC.